TUMBUH KEMBANG TUMBUHAN DALAM PERSPEKTIF TAFSIR ILMI (STUDI PENAFSIRAN FAKHR AL-DIN AL-RAZI) - Ghozi Mubarok; Ruly Pebri Andini Putri (AL-BAYAN INSTITUTE, 2026)
This study examines Fakhr Al-Din Al-Razi's interpretation of the process of plant growth and development from the perspective of scientific interpretation, focusing on the verses of QS. Al-An‘am: 95 and 99, Al-Hajj: 5, Ar-Raḥman: 6, and Al-Ḥijr: 22. The purpose of this study is to analyze how al-Razi explains the process of plant growth in Tafsir Mafatiḥ Al-Ghaib and to identify the characteristics of scientific interpretation he uses. This study aims to analyze how Fakhr Al-Din Al-Razi interprets the process of plant growth and development in Tafsir Mafatiḥ Al-Ghaib and to identify the characteristics of scientific interpretation he applies. This study uses qualitative research in the form of library research using books and other literature where Tafsir Mafatiḥ Al-Ghaib is the main data source. The characteristics of Fakhr Al-Din Al-Razi's scientific interpretation combine science with theology through the taḥlili method, examining verses from linguistic, legal, theological, and philosophical aspects. He interpreted the growth and development of plants as evidence of the order of Allah SWT's creation, where the process occurs according to the law of cause and effect established by Him. Elements such as water, wind, and soil play an important role in growth, while the final result, fruit, reflects His greatness. His rational and philosophical approach remains careful not to get caught up in changeable scientific interpretations, emphasizing that the Qur'an has a broader meaning than just science